Don't mention the war : the Australian Defence Force, the media and the Afghan conflict - Foster, Kevin D. (Kevin Dennis), 1961- (Investigating power series., 2013)
Don't Mention the War examines Australian media coverage of the war in Afghanistan. The book demonstrates how the military's public affairs personnel have taken over many of the roles traditionally performed by reporters and shows the restrictive affect of this on media coverage. This tight media management is contrasted with the more open approach of Dutch and Canadian militaries in Afghanistan, a fact that is explained through reference to the different positions of the military within these different nations. As opposed to the Dutch and the Canadians, who had reputations to rebuild, the almost uniquely exalted position of the military in Australia has enabled and driven a media strategy tailored to defend the Australian military's high social standing. In Australian media coverage, the book goes on to argue, the war in Afghanistan has then functioned as another platform for the celebration of national military virtues. What has been offered is less a representation of action than an affirmation of identity; less a chronicle of unfolding events than a testament to immutable character. "Foster argues convincingly that the ADF's determination to keep an iron grip on information, based on an entrenched cultural distain for journalists, a resistance to scrutiny, and an obsession with protecting its reputation, meant that what it was actually doing in Afghanistan remained a mystery. While he attributes authorship of this mystery to the ADF hierarchy, supported at times by politicians, journalists don't escape his censure. His book is an indictment of the lack of commitment by Australian editors to covering the Afghan war."--Tom Hyland, Inside Story, January 2014.